MIMO Antenna Design with Defected Ground Structure and Stub Slot for 5G Application - Sherila, Ayu Mika (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2025)
5G technology has been developed to address challenges and meet the demands for improved network efficiency and capacity, higher data rates, wider coverage, and lower power consumption. Therefore, an appropriate antenna design is essential for 5G wireless communication, capable of providing wide bandwidth, optimal radiation patterns, high antenna efficiency, and overall strong performance. The Multiple-Input Multiple-Output (MIMO) system, which utilizes multiple transmitting and receiving antennas, allows for more effective exploitation of multipath propagation. However, closely spaced antenna elements can lead to mutual coupling. Thus, the main challenge in designing MIMO antennas is to minimize the effects of mutual coupling. In this study, a MIMO antenna was designed using the Defected Ground Structure (DGS) technique and stub slots. The DGS technique was applied by modifying the antenna's ground plane to enhance its performance. To achieve wide bandwidth and high gain, the DGS and stub slot concepts were integrated into the antenna design. The antenna has dimensions of 84 mm × 34 mm and was simulated using Ansys HFSS software. The testing results showed that the antenna with an FR4 Epoxy substrate achieved a mutual coupling value of –30.65 dB, a return loss of –14.15 dB, a gain of 5.23 dB, and a sufficiently wide bandwidth. Therefore, this antenna is considered capable of operating at a frequency of 3.5 GHz and meets the requirements of 5G communication systems.